A validation study for wide-range remote assessment of cognitive functions in the healthy older Japanese population: a pilot randomised crossover trial - Yuki Takakura; Mika Otsuki; Ryo Takagi; Kiyohiro Houkin (BMC Geriatrics, 2023)
Abstract Background The assessment of a wide range of cognitive functions using video teleconference (VTC) systems cannot be applied in practice yet. We aimed to determine the feasibility and reliability of previously unvalidated remote cognitive function tests in Japan using common information and communication technology (ICT) devices, software, and VTC systems compared with face-to-face (FTF) assessment. Methods The sample consisted of 26 participants from senior citizens clubs and an employment service centre in Sapporo Japan, including 11 females and 15 males (age averaged 78.6 ± 6.8 years). Tests included the RCPM, Story recall, 10/36 spatial recall, selective reminding test, SDMT, PASAT, FAB, TMT-A, TMT-B, visual cancellation task, digit span, tapping span. The experimental design was a counterbalanced crossover randomised controlled trial. Intraclass correlations (ICCs), paired-samples t-tests, Cohen’s Kappa (κ) coefficients, and Wilcoxon signed-rank test were calculated to compare the scores between VTC and FTF assessments. Results All ICCs were significant and ranged from 0.47 (RCPM time) to 0.92 (RCPM score and PASAT), with a mean ICC of 0.75. Digit span using Cohen’s Kappa (κ) coefficient was significant, but the tapping span was not. Paired samples t-test showed statistically significant differences in SDMT, RCPM time, and cancellation time. Conclusions The results suggest that remote video conference-based neuropsychological tests even using familiar devices and software may be able to assess a wide range of cognitive functions in the Japanese older population. As for the processing speed tasks, we need to create our own standards for the remote condition. For the tapping span, we should consider increasing the number of trials.